Plasma miR-155, miR-203, and miR-205 are Biomarkers for Monitoring of Primary Cutaneous T-Cell Lymphomas - Dusílková, Nina; Bašová, Petra; Polívka, Jindřich; Kodet, Ondřej; Kulvait, Vojtěch; Pešta, Michal; Trněný, Marek; Stopka, Tomáš (International journal of molecular sciences, 2017)
Primary cutaneous T-cell lymphomas (CTCL) affect the skin and tend to transform and spread. CTCL involves primarily the Mycosis fungoides (MF) and more aggressive Sezary syndrome (SS). Oncogenic microRNAs (miRs) are stable epigenetic inhibitors often deregulated in the tumour and detectable as biomarkers in non-cellular fractions of peripheral blood. The tumour-specific expression of miR-155, miR-203, and miR-205 was shown to correctly diagnose CTCL. We herein asked whether these microRNAs can be used as plasma biomarkers for clinical CTCL monitoring. Patients with CTCL (n = 10) and controls with non-malignant conditions (n = 11) repeatedly donated plasma samples every ca. five months. MicroRNAs were detected in the plasma samples by specifically-primed RT-PCR followed by multivariate analyses of the miR expression dynamics. We herein established the plasma miR-classifier for detecting CTCL based on the miR-155 upregulation and miR-203/miR-205 downregulation with 100% specificity and 94% sensitivity. The 3-miR-score in the consecutive samples coincided with the clinical outcome of MF and SS patients such as the therapy response or changes in the clinical stage or tumor size. Quantitation of the selected microRNAs in plasma is a specific and straightforward approach for evaluating CTCL outcome representing, thus, a valuable tool for CTCL diagnostics and therapy response monitoring.
Keywords: mužské pohlaví; MicroRNAs; Liquid Biopsy; Male; senioři; senioři nad 80 let; výsledek terapie; atopic dermatitis; mikro RNA; Female; Humans; Neoplasm Staging; kůže; Prognosis; Skin; staging nádorů; lidé; kožní T-buněčný lymfom; stanovení celkové genové exprese; Biomarkers, Tumor; Middle Aged; nádorové biomarkery; ženské pohlaví; lidé středního věku; tekutá biopsie; Antineoplastic Combined Chemotherapy Protocols; Circulating MicroRNA; Sezary syndrome; prognóza; studie případů a kontrol; Case-Control Studies; Aged, 80 and over; microRNA; Lymphoma, T-Cell, Cutaneous; Treatment Outcome; protokoly protinádorové kombinované chemoterapie; Gene Expression Profiling; Psoriasis vulgaris; mycosis fungoides; cirkulující mikroRNA; cutaneous T-cell lymphomas (CTCL); Aged